A cross-sectional study to understand the pervasiveness of psychiatric features among tinnitus and vertigo patients - Ammar Ahmed; Muhammad Aqeel; Naeem Aslam; Bashir Ahmed (Journal of the Pakistan Medical Association, 2021)
Objective: To identify the psychiatric features among patients having tinnitus and vertigo symptoms due to vestibulocochlear disturbances. Methods: A cross-sectional study was conducted on Vestibulocochlear disorder Patients aged 18 Years and above, having chief symptoms of vertigo and tinnitus for the past 3 months. Patients having any cardiac linked disease and experiencing side effects of some medicines were excluded from the study. Present study spanned from May to September, 2019 at Hearts International Hospital, Rawalpindi and Hearing and Balance clinic, Rawalpindi in collaboration with the Foundation University, Islamabad. Ethical approval was obtained from the ethics committee of the Psychology department of Foundation University, Islamabad. Psychiatric evaluation was conducted by incorporating Tinnitus Handicap Inventory (THI), Dizziness Handicap Inventory (DHI) and Depression, Anxiety, Stress Scale (DASS). Audiological evaluations were carried out to gauge the severity of symptoms. Results: Of the 202 subjects, 60 were female (30%) and 142 were male (70%), fulfilling the inclusion criterion. It was found that patients experiencing vertigo and tinnitus symptoms had a strong tendency to develop psychiatric problems such as stress, anxiety and depression. Significant differences were noted among male and female patients regarding the representation of psychiatric symptoms. Conclusion: Various factors contribute and interfere in the psychological process that further contribute and aggravate the severity and symptoms of tinnitus and vertigo. Patients experiencing symptoms like tinnitus and vertigo in this domain tend to have a deviant psychological profile that is analogous with other chronic diseases. Continuous...